The The Effect of COVID-19 Vaccine Education with Audiovisual Media on Anxiety Levels of Pregnant Women as Candidates for COVID-19 Vaccination Participants - Putri Nurul Fikriyah; Dini Kurniawati; Nuning Dwi Merina (Nursing and Health Sciences Journal (NHSJ), 2023)
Giving the Covid-19 vaccine to pregnant women causes anxiety for pregnant women. One of the interventions that can be given is education using audiovisual media. This study aims to analyze the effect of audiovisual Covid-19 vaccine education on the anxiety level of pregnant women as potential participants for the Covid-19 vaccination in the work area of the Paleran Health Center. This study used a quasi-experimental with a pretest-posttest control group. The sample of this study was 84 pregnant women and used purposive sampling. The data was obtained using an anxiety questionnaire (validity=0.38 and reliability=0.93). The Wilcoxon test showed that there was an effect of education using audiovisual media (p=0.000). While in the control group, there was no effect (p=0.988). Mann-Whitney showed a significant difference between the intervention group after being given audiovisual media education and the control group (p=0.002). Audiovisual media is attractive and easy to understand because it can stimulate sight and hearing someone curious about the video that aired and got the information that affects mentality and behavior, so decrease anxiety level. in this case, audiovisual media will reduce pregnant women's anxiety about the Covid-19 vaccine.